A Bacchid at Apollonia: a late survival of an ancient family - MacDonald, David (KOINON: The International Journal of Classical Numismatic Studies, 2019)
A drachm struck late in the 1st century BC at Apollonia in Illyria testifies to the survival there of a branch of the Bacchids, a family first prominent at Corinth over half a millennium earlier. The origins of the Corinthian Bacchids are mythic. They claimed descent from Herakles, whose family, the Heracleids, was supposedly exiled from Greece after his death and returned in force some generations later. Earlier classicists equated the return of the Heracleids with the invasion of speakers of the Dorian Greek dialect; today even the reality of the Dorian invasion is vigorously contested.